2020
DOI: 10.1128/jb.00687-19
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsically Disordered Region of ExbD Is Required for Signal Transduction

Abstract: The TonB system actively transports vital nutrients across the unenergized outer membranes of the majority of Gram-negative bacteria. In this system, integral membrane proteins ExbB, ExbD, and TonB work together to transduce the proton motive force (PMF) of the inner membrane to customized active transporters in the outer membrane by direct and cyclic binding of TonB to the transporters. A PMF-dependent TonB-ExbD interaction is prevented by 10-residue deletions within a periplasmic disordered domain of ExbD ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 71 publications
(168 reference statements)
1
13
0
Order By: Relevance
“…The causal role of this mutation was proven by the observation that a complementation of ExbB Q163*, but not wild type of ExbB, into a Δ exbB strain conferred resistance to 27 . Previous studies showed that ExbB is an integral cytoplasmic membrane (CM) protein with three transmembrane domains. , It is believed that ExbB has three functions: as a scaffold on stabilizing the structure of Ton machinery, supplier of proton motive force (PMF) for conformational changes of TonB and the associated outer membrane receptor, and signal transduction. , ExbB Q163* is a truncated form of ExbB lacking the third transmembrane domain (TMD3) and the cytoplasmic carboxy terminus. By site-directed mutagenesis, Baker et al found key residues located in the three TMDs of ExbB and proposed that TMD 1 mainly interacts with the TMD of TonB, TMD 2 interacts with ExbD, whereas TMD 3 is involved in signal transduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causal role of this mutation was proven by the observation that a complementation of ExbB Q163*, but not wild type of ExbB, into a Δ exbB strain conferred resistance to 27 . Previous studies showed that ExbB is an integral cytoplasmic membrane (CM) protein with three transmembrane domains. , It is believed that ExbB has three functions: as a scaffold on stabilizing the structure of Ton machinery, supplier of proton motive force (PMF) for conformational changes of TonB and the associated outer membrane receptor, and signal transduction. , ExbB Q163* is a truncated form of ExbB lacking the third transmembrane domain (TMD3) and the cytoplasmic carboxy terminus. By site-directed mutagenesis, Baker et al found key residues located in the three TMDs of ExbB and proposed that TMD 1 mainly interacts with the TMD of TonB, TMD 2 interacts with ExbD, whereas TMD 3 is involved in signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that ExbB is an integral cytoplasmic membrane (CM) protein with three transmembrane domains. 46,51 It is believed that ExbB has three functions: as a scaffold on stabilizing the structure of Ton machinery, supplier of proton motive force (PMF) for conformational changes of TonB and the associated outer membrane receptor, and signal transduction. 46,47 ExbB Q163* is a truncated form of ExbB lacking the third transmembrane domain (TMD3) and the cytoplasmic carboxy terminus.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…Recent studies have highlighted the importance of the disordered, periplasmic linker domain of Ec ExbD. A conserved motif just upstream of the TM domain of E cExbD, V45, V47, L49, and P50 was found to be required for Ton function ( Kopp and Postle, 2020 ). The TonB periplasmic linker is long enough to allow the C-terminal folded domain of TonB to reach the TBDTs in the OM.…”
Section: Structures Of the Ton Complexmentioning
confidence: 99%
“…Both systems are also hijacked by bacteriocins for cell entry. Even though ExbBD-TonB does not display preference for the septal region (45), some degree of cross complementation has been reported between ExbBD and TolQR (46)(47)(48)(49)(50), indicative of possible interchangeability across the IM subcomplexes. In this work, we engineer a chimeric version of TonB-TolA that can work with the ExbBD subcomplex in Escherichia coli, giving rise to an assembled IM complex that no longer localizes specifically to the cell division site.…”
Section: Introductionmentioning
confidence: 99%